Anthropogenic influences on mercury in Chinese soil and sediment revealed by relationships with total organic carbon. (December 2019) - Xue, Wen; Kwon, Sae Yun; Grasby, Stephan E.; Sunderland, Elsie M.; Pan, Xin; Sun, Ruiyang; Zhou, Ting; Yan, Haiyu; Yin, Runsheng
Abstract: Rapid industrialization has led to high levels of mercury (Hg) releases from anthropogenic sources in China. When deposited to terrestrial ecosystems, Hg has a high affinity for natural organic carbon. This means that Hg concentrations will vary naturally as a function of the total organic carbon (TOC) content of different soils and sediment. Thus, Hg to TOC ratios in topsoil and surface sediment provides a useful normalized tracer of the anthropogenic impact on Hg contamination. We compiled literature-documented Hg and total organic carbon (TOC) data for topsoil ( n  = 957) and surface sediment ( n  = 1142) in China. Topsoil samples (n = 100) were also collected in this study to broaden the spatial coverage. We found large differences in Hg:TOC ratios among topsoil from background sites, agricultural and urban areas, and mining sites and surface sediment from fluvial, coastal, and marine environments. Specifically, a significant increase in Hg:TOC ratios occurred between soils from background sites (median: Hg:TOC = 21.1; Inter-Quartile Range (IQR): 9.67 to 40.7) and agricultural areas (median: 34.1; IQR: 22.1 to 58.7), urban areas (median: 62.1 ng g −1 ; IQR: 34.2 to 154) and mining sites (median: 2780; range: 181 to 43500). Urban and mining sites show the largest increase in Hg:TOC ratios, reflecting elevated anthropogenic Hg inputs in these areas. Fluvial sediment showed higher Hg:TOC ratios (median: 197; IQR: 109 to 389) than coastal (median: 88.3; IQR: 46.8 to 168) and marine sediment (median: 89.7; IQR: 53 to 138), indicating decreased anthropogenic Hg input from rivers to coastal and marine regions. Results of our study suggest Hg:TOC ratios are a useful normalized indicator of the influence of anthropogenic Hg releases on Hg enrichment in topsoil and surface sediment. Graphical abstract: Image 1 Highlights: Fluvial sediment showed higher Hg:TOC ratios than coastal and marine sediment. Hg:TOC ratios increased between soils from background sites, agricultural areas, urban areas and mining sites. Hg:TOC ratios are a useful normalized indicator of the influence of anthropogenic Hg.